Salivary cytokine profile in patients with oral lichen planus = Perfil de citoquinas salivales en pacientes con liquen plano oral - Martins Humberto, Janaina Silva
This study aimed to determine salivary concentrations of interleukin (IL)-1β, IL-2, IL-10, IL-23, transforming growth factor (TGF)-β, tumor necrosis factor (TNF)-α, nitrate (a by-product of nitric oxide oxidation), and cortisol in patients with oral lichen planus (OLP). Twenty patients diagnosed with OLP and 20 sex-matched healthy volunteers (HV) were included in this cross-sectional study. Unstimulated whole saliva was collected in the morning. Salivary cytokine and cortisol concentrations were determined by enzyme-linked immunosorbent assays (ELISA). Nitrate was measured in a nitric oxide analyzer. We found higher salivary concentrations of IL-2 (p<0.003), IL-23 ( p<0.04), and TGF-β (p=0.05) in patients with OLP compared to HV. No significant differences were found in salivary levels of TNF-α, IL-1β, or IL-10. Nitrate concentrations were markedly increased in OLP patients (1,227.0 ± 738.8 μM/mg total protein) when compared to HV (261.6 ± 166.8 μM/mg; p<0.0001). Salivary cortisol levels were also higher in OLP patients (2.79 ± 1.39 vs. 1.94 ±1.21 ng/mg; p<0.048). The markedly increased salivary levels of nitric oxide in patients with OLP suggest a relationship of this molecule with the cell death and tissue damage observed in these lesions.